ANALISIS AKAD IJARAH MUNTAHIYABITTAMLIK DALAM PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF DI INDONESIA - Munif, Nasrulloh Ali (An-Nisbah: Jurnal Ekonomi Syariah, 2017)
The rapid development of  the Islamic banking industry requires experts of Islamic economics and Islamic banking industry players to be more innovative.One form of  action of  these challenges is the emergence of  a new contract is acontract agreement Ijarah Al muntahiya bit Tamlik (IMBT)/financial leasingwith purchase. This contract is a contract is a hybrid combination of  proprietarylease agreement at the end of  the lease (sale and purchase agreement). Thiscontract became the new breakthrough and provides much convenience forcustomers, but the existence of  the contract IMBT still doubted by many. In general, they questioned how the legal basis of  IMBT both Islamic law and positive law in Indonesia. In the perspective of  Islamic law IMBT said tohave met the principles, pillars and three terms of  the contract. Kontemporeeconomic thinkers such as Adimarwan, Al-Mujamma ‘al-Fiqhi, and classicaleconomic thinkers such as Hanabillah, Malikiyah, Shafi’ites and HanabalahIMBT contract states that the law is permissible (allowed). When viewedfrom the standpoint of  positive law in Indonesia contract IMBT includedin the agreement is not named (Article 1319) arising from the principle of freedom of  contract (Article 1338) and IMBT also meets the requirements of  a valid agreement (Article 1320) as well as elements agreement. The legal consequences arising from the contract agreement IMBT is their right andobligation for them to do so.Pesatnya perkembangan industri perbankan syariah mensyaratkan para ahliekonomi Islam dan pelaku industri perbankan syariah untuk lebih inovatif.Salah satu bentuk tindakan tantangan ini adalah munculnya kontrak baruyaitu perjanjian kontrak Ijarah Al Muntahiya Bit Tamlik (IMBT)/sewakeuangan dengan pembelian. Kontrak ini merupakan kontrak kombinasi(hibrida) dari perjanjian sewa milik pada akhir sewa (perjanjian jual beli).Kontrak ini menjadi terobosan baru dan memberikan banyak kemudahan bagipelanggan, tetapi keberadaan IMBT kontrak masih diragukan oleh banyakpihak. Pada umumnya, mereka mempertanyakan bagaimana dasar hukumIMBT baik hukum Islam dan hukum positif  di Indonesia. Dalam perspektif hukum Islam IMBT dikatakan telah memenuhi prinsip-prinsip, pilar dantiga syarat-syarat dalam kontrak. Para pemikir ekonomi Kontemporerseperti Adimarwan, Al-Mujamma al-Fiqhi, dan pemikir ekonomi klasikseperti Hanabillah, Malikiyah, Syafi’iyah dan kontrak Hanabalah IMBTmenyatakan bahwa hukum IMBT diperbolehkan. Bila dilihat dari sudutpandang hukum positif  di IMBT kontrak Indonesia termasuk dalamperjanjian tidak bernama (Pasal 1319) yang timbul dari prinsip kebebasanberkontrak (Pasal 1338) dan IMBT juga memenuhi persyaratan perjanjianyang sah (Pasal 1320) sebagai serta perjanjian elemen. Konsekuensi hukumyang timbul dari IMBT perjanjian kontrak adalah hak dan kewajiban mereka bagi mereka untuk melakukannya.